Analysis of Coastline Changes with the Utilization of Geospatial-Based Sentinel Imagery - Karlos, Birto; Belladona, Meilani; Supriyono (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2025)
Coastline is a dynamic phenomenon influenced by natural forces such as waves, currents, tides, and human activities such as coastal resource extraction and infrastructure development. Using Sentinel-2 imagery and geospatial technology, this study seeks to examine the changes in the coastline in the coastal areas of Lais, Air Besi, and Air Napal Districts, North Bengkulu Regency. The approach used includes image processing with geometric correction, Normalized Difference Water Index (NDWI), coastline digitization, and accuracy testing using a fusion matrix. The results of the analysis show that between 2019 and 2024 there will be considerable changes in the coastline, with an average erosion rate of 1,71 Meters per year. Some areas, such as Pasar Bembah 2.39 meters per year, Pal-30 2,182 meters per year, and Air Padang Village 3,293 meters per year, have experienced significant erosion. Air Padang Village is among the areas most affected by abrasion. Limiting human activities in areas prone to abrasion, planting coastal vegetation, and building sea walls are important strategies that can be used to reduce the impact of abrasion and shoreline changes.